Chromium-containing small pore mesoporous silicas: synthesis, characterization and catalytic behavior in the liquid phase oxidation of cyclohexane - Shylesh, S.; Samuel, Prinson P.; Singh, A. P. (Applied Catalysis A-General, 2007)
Organic-inorganic hybrid mesoporous silica materials containing chromium and various organo trialkoxysilanes (chloropropyl, vinyl, methyl) were prepared by the co-condensation method, in the presence of cetyl trimethyl ammonium surfactants. The hybrid material, containing chromium, retains one X-ray diffractogram (XRD) peak up to a molar ratio of 1: 1 between tetra ethyl orthosilicate (TEOS) and organosilane in the synthesis gel. Small pore mesoporous chromium-silica samples can be prepared from the large pore hybrid mesoporous chromium samples by calcination. By this method, the pore size of the material can be tailored into the supermicroporous region, without changing the chain length of the surfactant used in the assembly process, as judged from the XRD and N-2 sorption isotherms. The shrinkage in pore size is dependent on the nature and percentage of the organic pendant groups, such that the chloro propyl and vinyl pendant mesoporous material show more pore size shrinkage than the smaller methyl pendant units. Because of the tailorable pore size and with better textural characteristics, the chromium samples show better catalytic activity in the aerial oxidation reaction of cyclohexane than the conventional chromium-containing mesoporous material, like Cr-MCM-41, under a solvent free system. Among the porous chromium catalysts, the samples prepared using chloro propyl silane show higher cyclohexane conversion and cyclohexanone selectivity and behave as a true heterogeneous catalyst. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: chromium; Cyclohexane; Oxidation; small pore silicas